Efektivitas Penggunaan Model Pembelajaran Probing-Prompting Terhadap Hasil Belajar Siswa Tema Lingkungan Sahabat Kita di Kelas V Sekolah Dasar - Setiawan, Angga (Universitas Nusantara PGRI Kediri, 2021)
This study aims to determine the effectiveness of the use of the probing-prompting learning model on student learning outcomes on the theme Our Friends of the Environment in grade V Elementary School. This study uses a quantitative method with a quasy experimental research type. Population and sample of all students in grade V with a total of 17 students. The data obtained by observation, pretest (pre-test) aims to determine student learning outcomes before being given treatment and posttest (final test) to determine student learning outcomes after being given treatment. The research instrument used the pretest and posttest questions. Data analysis using t-test, t-test results on learning outcomes obtained t count> t table that is 3.29> 2.09 with a confidence level of 95%. Meanwhile, the influence of variable X (probing-prompting learning model) on variable Y (learning outcomes) is 76.7%. With these results, the alternative hypothesis is accepted and the null hypothesis is rejected. It can be concluded that there is a significant effect of the probing-prompting learning model on student learning outcomes in the theme of our best friend's environment in grade V elementary school.